2010
DOI: 10.1111/j.1365-2516.2010.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrotherapy: yesterday, today and tomorrow

Abstract: Summary. The use of electrotherapy has been part of physical therapy treatment for the past few decades. There have been numerous modalities used such as TENS, interferential, diathermy, magnetic therapy, ultrasound, laser and surface electromyography to name a few. There has been an upsurge in the past decade of new and innovative modalities. There needs to be extensive research on each of these electrotherapy devices to determine the proper use of each device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 13 publications
1
33
0
2
Order By: Relevance
“…These results are consistent with Tiktinsky et al [43] that showed PEMF relieved pain effectively in joint problems of 38 patients with hemophilia. In addition, the ROM of these painful joints and the patients' walking abilities improved significantly.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with Tiktinsky et al [43] that showed PEMF relieved pain effectively in joint problems of 38 patients with hemophilia. In addition, the ROM of these painful joints and the patients' walking abilities improved significantly.…”
Section: Discussionsupporting
confidence: 94%
“…There are a wide variety of physiological and cellular level effects that have been shown to be the result of laser treatment. Some include increased cellular metabolism, stimulation of macrophages, stimulation of mast cell degranulation, activation and proliferation of fibroblasts, and alteration of cell membrane potentials [43].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The use of electrical energy for therapeutic purpose goes back as far as the 18 th century. 5 Electrotherapy has been used for treating different medical conditions 6 . For example, use of diathermy for treating various gynaecological conditions 7 such as the use of microwave diathermy before conception and during early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous literature, although primary outcome was generally measured at a certain time point, the average score reflected the average level of pain during the last week, which was thus more meaningful than other methods of measuring single time point due to recurrence of sciatica. The control group underwent MFE, which exerts its effect via the stimulation or activation of physiological events by applying energy, thereby producing therapeutic benefits that facilitate pain relief [28]. Mechanisms leading to pain relief may be due to a variety of peripheral effects of control activity, on the spinal and spinal nervous system.…”
Section: Discussionmentioning
confidence: 99%